Intrauterine Infections and the Risk of Neurological Disorders in Newborns (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Intrauterine infections represent a significant risk factor for the development of neurological disorders in newborns. These infections, caused by viruses, bacteria, fungi, or parasites, can be transmitted transplacentally, ascending from the birth canal, or during delivery. Pathogenic mechanisms include direct neural damage, inflammatory responses, hypoxia, ischemia, and metabolic disturbances, all of which can impair brain development. Common intrauterine infections, summarized under the TORCH acronym, include Toxoplasma gondii, other agents (syphilis, varicella, parvovirus B19), Rubella, Cytomegalovirus, and Herpes simplex virus. Clinical manifestations in affected neonates range from psychomotor developmental delay and seizures to microcephaly, hypotonia, and sensory deficits. Timely prenatal diagnosis, maternal vaccination, targeted antiviral or antibacterial therapy, and comprehensive postnatal care are essential for reducing long-term neurological sequelae. This review emphasizes the importance of early detection, preventive strategies, and multidisciplinary management to improve neurodevelopmental outcomes in newborns exposed to intrauterine infections.